(untitled) (Medical Forum Monthly, 2024)
Objective: To measure the synergistic effects of Aloe vera and Rosiglitazone on blood glucose, insulin and insulin insensitivity in non-insulin dependent diabetes mellitus. Study Design: Randomized control trail study Place and Duration of Study: This study was conducted at Army Medical College, Rawalpindi in the Physiology Department from January 2009 to September, 2010 in alliance with National Institute of Health (NIH) Islamabad Materials and Methods: Thirty healthy rats were made diabetic according to Srinivasan model. After confirming type 2 diabetes in them they were randomly segregated into two equal groups. The groups named diabetic were injected with normal saline and other combined group were given 150mg/kg body weight of Aloe vera extract and 2.5mg/kg body weight of rosiglitazone diabetic group. It was half their effective dose as their effective dose was calculated through pilot study. Results: Plasma glucose, insulin, and TG/HDL ratio were significantly reduced (p<0.0000001) in combined group then diabetic control group Conclusion: The significant result was obtained in combined group in lowering plasma glucose, insulin and insulin resistance though half their effective doses were used. It will also help in reducing side effects associated with use of rosiglitazone.